Geometry and martingales in Banach spaces - Woyczyński, W. A. (Wojbor Andrzej), 1943- (Boca Raton, Florida : CRC Press, 2018)
"This book provides a compact exposition of the results explaining the interrelations existing between the metric geometry of Banach spaces and the theory of martingales with values in those Banach spaces"--
8.1 General definitions and properties and their rela-tionship to types of Banach spaces8.2 Local structure of B-convex spaces and preservation of B-convexity under standard operations; 8.3 Banach lattices and reflexivity of B-convex spaces; 8.4 Classical weak and strong laws of large numbers in B-convex spaces; 8.5 Laws of large numbers for weighted sums and not necessarily independent summands; 8.6 Ergodic properties of B-convex spaces; 8.7 Trees in B-convex spaces; 9 Marcinkiewicz-Zygmund Theorem in Banach spaces; 9.1 Preliminaries
OCLC-licensed vendor bibliographic record.
Keywords: Martingales (Mathematics); Geometric analysis; Banach spaces; MATHEMATICS / Applied; MATHEMATICS / Probability & Statistics / General